Analyzing the Impact of Academic and Financial Factors on the Employment Prosperity of Engineering Graduates: A Case Study from Universitas Negeri Yogyakarta - Indrihapsari, Yuniar; Luthfi, Muhammad Irfan; Ardy, Satya Adhiyaksa; Shittu, Abdul Jaleel Kehinde (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
The rapid technological advancements and evolving job markets present a pressing need to understand how academic experiences shape the career outcomes of engineering graduates. This understanding is crucial for educational institutions aiming to align their curricula with industry demands and for graduates seeking to maximize their career prospects. Notably, the role of financial support, academic performance, and early career experiences in influencing graduate prosperity remains underexplored. This study aims to analyze the correlation between finance support, GPA, study period, job waiting times, salary details, and the prosperity of graduates from the Faculty of Engineering at Universitas Negeri Yogyakarta. The prosperity of graduates is defined as earning wages equal to or exceeding the Indonesian minimum average wage. Using data from a tracer study questionnaire, the research employed logistic regression and correlation analysis to investigate these relationships. The data underwent several stages of filtering, resulting in a refined dataset of 70 records for analysis. This study used SPSS software for statistical analysis, focusing on descriptive statistics, correlation, and logistic regression models. The results highlighted significant predictors of graduate prosperity, including GPA and types of financial support, while illustrating the limited predictive power of early career experiences on long-term earnings. The study also indicated that extended study periods do not necessarily correlate with higher wages. In conclusion, the study underscores the importance of targeted educational strategies and student support systems that are responsive to the dynamics of the job market, enhancing the readiness and prosperity of engineering graduates.